Evaluation of pulmonary artery bleeding during thoracoscopic pulmonary resection for lung cancer. Issue 21 (17th September 2022) - Tomoyasu, Makoto; Deguchi, Hiroyuki; Kudo, Satoshi; Shigeeda, Wataru; Kaneko, Yuka; Yoshimura, Ryuichi; Kanno, Hironaga; Saito, Hajime
Abstract: Background: Bleeding from the pulmonary artery (PA) can be fatal in video‐assisted thoracoscopic surgery (VATS) for lung cancer. We evaluated intraoperative PA injury and assessed precautions for thoracoscopic anatomic pulmonary resection. Methods: We retrospectively analyzed a total of 1098 patients who underwent radical surgery for lung cancer utilizing complete VATS from January 2010 to December 2021. Results: A total of 16 patients (1.5%) had PA injury during VATS, while hemostasis was performed by conversion to thoracotomy in eight patients (50.0%). Although there was a significantly greater operation time and blood loss for patients in the PA injury group (318.4 vs. 264.9 min, p = 0.001; 550.3 vs. 60.5 g, p ≤ 0.001, respectively), there was no significant different for the chest tube insertion duration and length of postoperative hospital stay (4.9 vs. 7.8 days, p = 0.157; 10.6 vs. 9.9 days, p = 0.136, respectively). There was a significant difference observed for the surgical procedure related to the left upper lobectomy in the PA injury group (43.8 vs. 18.8%, p = 0.012), with the primary causative PA determined to be the left anterior segmental PA (A 3 ) (31.3%). Conclusions: VATS is both feasible and safe for lung cancer treatment provided the surgeon performs appropriate hemostasis, although fatal vascular injury could potentially occur during VATS. Surgeons need to be aware of the pitfalls regarding PA dissection management. Abstract : Pulmonary artery (PA) injury during video‐assisted thoracoscopic surgery was relatively occurred left upper lobectomy (LUL), especially left A 3 injury. Bleeding control in pulmonary resection is a fundamental challenge, and this retrospective study also confirmed that LUL is prone to accidents as per the surgeon's impression. It is a report as one of the data for building more clear evidence.